Pengaruh Kemampuan Manajerial Kepala Madrasah, Kompensasi Guru, dan Budaya Kerja Kementerian Agama Terhadap Kinerja Guru Madrasah Tsanawiyah Di Kabupaten Batu Bara - Syahputra, Dermawan; Hadijaya, Yusuf; Syukri, Makmur (Jayapangus Press, 2024)
The research is motivated by the number of teachers who do not do their assignments well, the number of teachers who are late even though there is time for morning teaching, there are still many teachers who do not complete their work on time, there are teachers who are not able to make learning tools, including the creation of annual programs, semester programs, syllabi, and learning program plans (RPP). This research aims to improve the quality of teacher performance in the classroom by integrating human values in work, especially how well the orientation of the managerial ability of madrasah heads, teacher compensation and the work culture of the Ministry of Religion in achieving better teacher performance. Quantitative research with the expost facto method was carried out at Madrasah Tsanawiyah in Batu Bara Regency, namely 36 madrasas. The researcher gave several variable questionnaires to madrasah teachers, each of which had been adjusted to variable indicators. The researcher processed the data by classification assumption test, t-test, F test and R2 test using the SPSS version 25 program. This study reveals (1) The managerial skills of madrasah heads have a positive effect on teacher performance; (2) Teacher compensation has a positive effect on teacher performance; (3) The work culture of the Ministry of Religion has a positive effect on teacher performance; (4) The managerial skills of madrasah heads and teacher compensation have a positive effect on teacher performance; (5) The managerial ability of the head of the madrasah and the work culture of the Ministry of Religion have a positive effect on teacher performance; (6) Teacher compensation and work culture of the Ministry of Religion have a positive effect on teacher performance and (7) The managerial ability of madrasah heads, teacher compensation and work culture of the Ministry of Religion have a positive effect on teacher performance.